Effects of chronotherapy on circadian rhythm and ADHD symptoms in adults with attention-deficit/hyperactivity disorder and delayed sleep phase syndrome: a randomized clinical trial. (1st February 2021) - van Andel, Emma; Bijlenga, Denise; Vogel, Suzan W. N.; Beekman, Aartjan T. F.; Kooij, J. J. Sandra
ABSTRACT: The majority of adults with Attention-Deficit/Hyperactivity Disorder (ADHD) have a delayed circadian rhythm that is a characteristic of Delayed Sleep Phase Syndrome (DSPS). Treatment of DSPS may improve both the circadian rhythm and ADHD symptoms. In this three-armed randomized clinical trial, 51 adults (18–55 y) with ADHD and DSPS received sleep education and 3 weeks of (1) 0.5 mg/d placebo, (2) 0.5 mg/d melatonin, or (3) 0.5 mg/d melatonin plus 30 minutes of 10, 000 lux bright light therapy (BLT) between 07:00 and 08:00 h. Placebo/melatonin conditions were double-blind. Treatment took place in the participants' naturalistic home settings. Dim-light melatonin onset (DLMO) was measured in saliva as marker of internal circadian rhythm. Melatonin or placebo administration followed individual schedules, starting 3 hours before the individual DLMO and weekly advancing by 1 h. DLMO and ADHD Rating Scale score were assessed at baseline, directly after 3-week treatment, and two weeks after the end of treatment. Results show that at baseline 77% had a DLMO after 21:00 h with an average DLMO at 23:43 h ± 1h46. Directly after treatment, melatonin had advanced DLMO by 1h28 ( p = .001), and melatonin plus BLT by 1h58 ( p < .001). Placebo did not affect DLMO. ADHD symptoms reduced by 14% ( p = .038) directly after melatonin treatment. Placebo and melatonin plus BLT did not impact ADHD symptoms. Two weeks after end of treatment, ADHD symptoms and DLMO had returned to baseline levels. It can be concluded that low doses of melatonin advanced the circadian rhythm and reduced self-reported ADHD symptoms. Given the large number of adult ADHD patients with concurrent DSPS, treating delayed sleep with melatonin is an important component of effective ADHD treatment.